A Novel Small-Molecule Inhibitor of SREBP-1 Based on Natural Product Monomers Upregulates the Sensitivity of Lung Squamous Cell Carcinoma Cells to Antitumor Drugs - Ma, De-Bin; Liu, Xing-Yu; Jia, Hui; Zhang, Yingshi; Jiang, Qiyu; Sun, Huiwei; Li, Xiaojuan; Sun, Fang; Chai, Yantao; Feng, Fan; Liu, Lei (Frontiers in Pharmacology, 2022)
The transcription factor, sterol regulatory element binding protein 1 (SREBP-1), plays important roles in modulating the proliferation, metastasis, or resistance to antitumor agents by promoting cellular lipid metabolism and related cellular glucose-uptake/Warburg Effect. However, the underlying mechanism of SREBP-1 regulating the proliferation or drug-resistance in lung squamous cell carcinoma (LUSC) and the therapeutic strategies targeted to SREBP-1 in LUSC remain unclear. In this study, SREBP-1 was highly expressed in LUSC tissues, compared with the paired non-tumor tissues (the para-tumor tissues). A novel small-molecule inhibitor of SREBP-1, MSI-1 (Ma’s inhibitor of SREBP-1), based on natural product monomers, was identified by screening the database of natural products. Treatment with MSI-1 suppressed the activation of SREBP-1-related pathways and the Warburg effect of LUSC cells, as indicated by decreased glucose uptake or glycolysis. Moreover, treatment of MSI-1 enhanced the sensitivity of LUSC cells to antitumor agents. The specificity of MSI-1 on SREBP-1 was confirmed by molecular docking and point-mutation of SPEBP-1. Therefore, MSI-1 improved our understanding of SREBP-1 and provided additional options for the treatment of LUSC.